The Development of Interactive Media Assisted by Macromedia Flash to Improve the Ability of Understanding the Fiction Story Information in Elementary School Students - Anggi Chairunnisa Siregar; Abdurahman Adisaputera; Anita Yus (BIRCU, 2020)
This study aims to: (1) Analyze the effectiveness level of interactive learning media assisted by Macromedia Flash on story text learning that will be developed at Public Elementary School 060856 Medan Perjuangan Subdistrict. (2) Analyze how the level of interactive learning media assisted by Macromedia Flash in story text learning that will be developed at Public Elementary School 060856 Medan Perjuangan Subdistrict. This study uses Borg & Gall development research. Based on the analysis of learning media products assisted by Macromedia Flash from the experts, it was declared very effective and feasible to use with criteria of the validity of the material experts 85.42%, the design expert 91.00%, and the linguist 85.00%. Based on the completeness data of student learning outcomes before using interactive learning media assisted by Macromedia Flash obtained an average score of 62 while after using a large scale completeness reached an average of 90 with a gain score of 0.74 into the high category. And the student questionnaire responses to the effectiveness of interactive learning media assisted by Macromedia Flash reached 90% of 30 students. Based on this data interactive learning media assisted by Macromedia Flash are said to be effectively used in learning with the assumption that students' understanding of story text is higher when using interactive learning media assisted by Macromedia Flash.